A REVIEW ON UNDERSTANDING OF DHAMANI - Swapna H N; Uma B Gopal; Swati S Bedeker (International Journal of Applied Ayurved Research, 2017)
Interpretation of Ayurvedic terminologies in contemporary science remains confusing in many contexts. Dhamani is one among such terminologies. Sushruta, the father of surgery, clearly explained the constitution of human body from Twak (skin) to Sookshma Srotas (mi-nute channels) and their enumeration, in which Sira (vein), Dhamani (artery), Srotas (capil-laries) are the channels for the transportation of Rasadi Dhatu (nutrient components). They are interpreted as blood vessels, lymphatic channels and nervous entity. In many context, Dhamani falls under the category of vascular entity. Mooka (dumb), Minmina (nasal twang) & Gadgada (stammering) manifest due to involvement of Shabdavahini Dhamani; thus it is considered as neurological entity. There arises confusion whether to consider Dhamani as neurological entity or vascular entity. Hence this study is aimed to emphasize on Dhamani as a specific anatomical structure by critically reviewing all possible literature, both as per Ayurveda and contemporary science.